2013
DOI: 10.1111/corg.12026
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Performance in Socially Responsible Corporations: New Empirical Insights from a Neo‐Institutional Framework

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: This paper investigates the relationship between corporate governance (CG) and corporate social responsibility (CSR), and consequently, examines whether CG can positively moderate the association between corporate financial performance (CFP) and CSR.Research Findings/Insights: Using a sample of large listed corporations from 2002 to 2009, we find that, on average, better-governed corporations tend to pursue a more socially responsible agenda through increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
602
12
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(688 citation statements)
references
References 138 publications
(489 reference statements)
59
602
12
15
Order By: Relevance
“…Entity governance has long been a topic of interest, and the impact of corporate governance is still largely unknown (Ntim & Soobaroyen 2013a). Prior studies have found that there are two large categories of corporate governance that have an effect on disclosure decisions, namely ownership structures and the board composition (Fifka 2011).…”
Section: Governancementioning
confidence: 99%
“…Entity governance has long been a topic of interest, and the impact of corporate governance is still largely unknown (Ntim & Soobaroyen 2013a). Prior studies have found that there are two large categories of corporate governance that have an effect on disclosure decisions, namely ownership structures and the board composition (Fifka 2011).…”
Section: Governancementioning
confidence: 99%
“…Ntim and Soobaroyen [73] focused on a sample of South African firms and found a positive influence of the board's independence on both CFP and CSP. Similarly, Dunn and Sainty [74] studied a sample of 104 Canadian firms and concluded that companies with more independent boards generally obtain higher levels of CSP.…”
Section: Linking Board Independence and Corporate Social Performancementioning
confidence: 99%
“…In a final step, those empirical studies that did not provided the required statistical data (i.e., correlation coefficients between the variables or the corresponding data to obtain them using Lipsey and Wilson´s [171] conversion method) were removed (73). The final sample included 87 papers.…”
mentioning
confidence: 99%
“…This may necessitate investment in CSR activities (Mohd Ghazali [17]). Ntim and Soobaroyen [18] report a negative relationship between close ownership and CSR disclosures. Al-Bassam et al [19] found a negative link between close ownership and corporate governance disclosures.…”
Section: Should Csr Be Mandatory?mentioning
confidence: 99%